(untitled) (Circe de clásicos y modernos, 2023)
In the following work, we propose a twofold objective: on the one hand, the historiographical analysis of the application of the concept of the “bipartite estate” in the history of Roman agriculture; on the other hand, the analysis of a specific case to which this concept could be applied: Horacio’s Sabine estate.